The impact of gender mismatching on early and late outcomes following heart transplantation. (30th August 2016) - Peled, Yael; Lavee, Jacob; Arad, Michael; Shemesh, Yedida; Katz, Moshe; Kassif, Yigal; Asher, Elad; Elian, Dan; Har‐Zahav, Yedael; Goldenberg, Ilan; Freimark, Dov
Abstract: Aims: The role of donor/recipient gender matching on the long‐term rejection process and clinical outcomes following heart transplantation (HT) outcomes is still controversial. We aim to investigate the impact of gender matching on early and long‐term outcome HT. Methods and results: The study population comprised 166 patients who underwent HT between 1991 and 2013 and were prospectively followed up in a tertiary referral centre. Early and late outcomes were assessed by the type of donor–recipient gender match (primary analysis: female donor–male recipient [FD–MR, n = 36] vs. male donor–male recipient [MD–MR, n = 109]). Early mortality, need for inotropic support, length of hospital stay, and major perioperative adverse events did not differ between the FD–MR and MD–MR groups. However, the FD–MR group experienced significantly higher rates of early major rejections per patient as compared with the MD–MR group (1.2 ± 1.6 vs. 0.4 ± 0.8; P = 0.001), higher rates of overall major rejections (16 vs. 5.5 per 100 person years; P < 0.05), and higher rate of cardiac allograft vasculopathy (43% vs. 20%; P = 0.01). Kaplan–Meier survival analysis showed that the cumulative probabilities of survival free of rejections and major adverse events were significantly higher in MD–MR group ( P = 0.002 and 0.001, respectively). Multivariate analysis showed that FD–MR status was associated with >2.5‐fold ( P = 0.03) increase in the risk for rejections and with a >3‐fold ( P = 0.01) increase in the risk for major adverse events during follow‐up. Conclusions: Donor–recipient gender mismatch is a powerful independent predictor of early and late rejections and long‐term major adverse events following HT.